(untitled) (Jalalabad Medical Journal, 2026)
Iron-chelation therapy is widely regarded as the primary option for reducing iron accumulation. Excessive accumulation of iron may significantly contribute to the morbidity and mortality with transfusion-dependent thalassaemia major. Two widely recognised iron chelators are deferoxamine and deferasirox, despite the presence of certain adverse effects. However, there is a lack of data regarding the impact of these medications on blood parameters. An observational study was carried out at the department of pharmacology and therapeutics, Sylhet MAG Osmani Medical College, Sylhet. The age of the enrolled children were 2-15 years with transfusion-dependent thalassaemia and serum ferritin levels exceeding 1500 ng/mL. The study included a total of 25 patients who received injectable deferoxamine (DFO) therapy and 26 patients who received oral deferasirox (DFX) treatment for a period of 6 months. Serum ferritin, serum creatinine, serum ALT and CBC were assessed at the beginning of the study and again after 6 months of treatment. Serum ferritin level was decreased significantly in both deferoxamine and deferasirox group (p<0.001). Haematological (haemoglobin, neutrophil and platelet count) and biochemical (serum creatinine, serum ALT) parameters did not change significantly (p<0.05). Deferoxamine and deferasirox reduced serum ferritin levels significantly but did not have any significant effect on blood parameters in children with iron overload who had transfusion-dependent thalassaemia. Jalalabad Med J 2025; 22 (1): 6-11